KAJIAN HUKUM PERKAWINAN CAMPURAN (AMALGAMASI) ANTARA SUKU MINANGKABAU DENGAN SUKU JAWA - Kartika Cahyaningtyas; Muh. Isra Bil Ali (LPPM institut Teknologi Bisnis AAS Indonesia, 2024)
This research examines and analyzes the laws of mixed marriages (amalgamation) that occur between the Minangkabau and Javanese tribes based on applicable regulations. This is because there are differences in principles where the Minangkabau tribe adheres to matrilineal principles, while the Javanese adhere to parental (bilateral) principles. The method used in normative research with research results is the setting of these principles, so the inheritance for future children who become heirs will also be different. If men from the Minangkabau tribe cannot inherit directly to their future children, women from the Javanese tribe can immediately inherit to their future children. This is because the matrilineal principle originates from the woman or mother, while the parental (bilateral) principle originates from the mother and father. Another thing is that you have to look at whether there are taboos or not, in this article there are no taboos and the Javanese can submit themselves to the Minangkabau tribe. Keywords: Mixed Marriage (Amalgamation), Matrilineal, Parental, Minangkabau Tribe, Javanese Tribe, Submission A. PENDAHULUAN